2016
DOI: 10.1111/trf.13712
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐dose intravenous immunoglobulins for the treatment of fetal and neonatal alloimmune thrombocytopenia: a cohort study

Abstract: In pregnancies with FNAIT with a previous affected child without ICH, treatment with IVIG in a weekly dose of 0.5 or 1.0 g/kg results in comparable neonatal PLT count at birth and degree of thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Universal screening for FNAIT is not recommended during the routine antenatal screening although FNAIT is not uncommon 22. Prenatal screening for FNAIT in highrisk population revealed an actual risk for FNAIT, and the prevention of maternal sensitization by the serial monitoring and immunosuppression with low-dose prednisone and short-term intravenous immunoglobulin G infusion (during the third trimester of the second pregnancy) resulted in two successful pregnancies in this case.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Universal screening for FNAIT is not recommended during the routine antenatal screening although FNAIT is not uncommon 22. Prenatal screening for FNAIT in highrisk population revealed an actual risk for FNAIT, and the prevention of maternal sensitization by the serial monitoring and immunosuppression with low-dose prednisone and short-term intravenous immunoglobulin G infusion (during the third trimester of the second pregnancy) resulted in two successful pregnancies in this case.…”
mentioning
confidence: 79%
“…30 Our results also showed that women with ITP had elevated TNFα/IL-10 and IFN-ϒ/IL-10 ratios. 16,22,29,31 However, only about 30% of the HPA-1anegative women with this HLA antigen are immunized. A 0 or Th2 pattern after IVIG gave the best prognosis, whereas sustained high expression of IFNγ and refractoriness to IVIG were the main indicators of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence accumulated regarding ITP, Kawasaki disease, GBS, and CIDP has led to FDA authorization. Furthermore, small‐scale studies had shown that many IVIG may provide benefit in many other autoimmune diseases . Despite its beneficial effects, the specific mechanism of action of IVIG remains unclear and probably modulates the immune system via multiple pathways …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, small-scale studies had shown that many IVIG may provide benefit in many other autoimmune diseases. 20,[31][32][33][34][35] Despite its beneficial effects, the specific mechanism of action of IVIG remains unclear and probably modulates the immune system via multiple pathways. 35,36 In 2012, 75% of IVIG was delivered to patients with autoimmune or inflammatory diseases in the United States.…”
Section: Immunomodulation Therapymentioning
confidence: 99%